Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.